Pengaruh Pelaksanaan Kepemimpinan, Komunikasi, Dan Lingkungan Kerja Fisik Terhadap Kepuasan Kerja Karyawan Pada Pt. Karang Bali Asli Tur Denpasar - Wahyudi, Wayan (E-Jurnal Manajemen; Vol 2 No 10 (2013), 2013)
The effect of a simultaneously significant, partial and dominant among the variables of leadership, communication, and physical work environment on job satisfaction of employees PT. Karang Bali Asli Tur. Sample 66 people. Based on the results of analysis show that the variables of leadership, communication, and physical work environment simultaneously or partially significant effect on job satisfaction of employees at PT. Karang Bali Asli Tur. Suggestions that can be conveyed companies should demonstrate leadership that is open, fair and able to establish a good relationship with the employees, the application of the continue effective communication between leaders and subordinates, as well as ensure and maintain a comfortable working environment within the company so as to improve the capacity, quality, and can create employee satisfaction. Keywords: communication, leadership, physical work environment, employee satisfaction